PHARMACOECONOMIC BENEFITS OF CYTOMEGALOVIRUS INFECTION PROPHYLACTIC STRATEGY FOR RENAL TRANSPLANT RECIPIENTS - V. V. Ryazhenov; S. G. Gorokhova (Вестник трансплантологии и искусственных органов, 2011)
CMV infection is a major problem in kidney transplantation patients. Valcyte, Cimevene are the first line thera- py of CMV infection. This pharmacoeconomic analysis shown economic benefits of Valcyte prophylaxis tactic compare preemptive strategy.